ARTIFICIAL INTELLIGENCE IN EDUCATION: OPPORTUNITIES AND CHALLENGES - Toshboltaev Fakhriddin Urinboevich; Minojiddinova Mukhlisa Ahrorjon qizi (PEDAGOGS, 2025)
Abstracts: This article discusses the use of artificial intelligence (AI) technologies in education, including their benefits and the problems they may cause. AI can help make learning more personal, check students’ knowledge automatically, and create educational platforms based on students’ needs. It also helps reduce teachers’ workload and improve the quality of lessons. However, using AI in education may also bring some problems. For example, the article talks about the protection of personal data, less human interaction, lack of technology, and ethical issues. It also looks at how these technologies are being used in the education system of Uzbekistan, their potential, and future development. The research shows that using AI in education can help improve digital skills and modern teaching methods. This makes the topic important both scientifically and practically.